Increasing Financial Literacy Through Basic Accounting Training for Small Medium Enterprises in the Riau Islands Province - Patmawati; Hasni Yusrianti; Rela Sari; Ahmad Fadhil Yusof; Hasna Nirwana; Ahmad Raihan Amin (PT. Altaf Publishing Corp, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, but in reality business actors still face challenges in financial management and financial literacy, one of which is MSMEs in the Riau Islands Province. Based on the analysis of the situation, the service team carried out this community service activity with the aim of improving the financial literacy skills of MSME actors in Riau Islands Province through basic accounting training. MSME actors really need this activity because there is still a lack of knowledge in the preparation of simple financial statements. The method of implementing activities was carried out by lectures illustations, illustrations, discussions, and questionnaire distribution. The results of the activity showed an increase in participants' understanding in compiling simple financial statements, separating personal and business finances, and implementing financial recording using Excel. Participants also showed interest in using digital tools and conveyed the need for advanced training in financial planning and online marketing. This activity proves that participatory and contextual community-based training can be an effective solution in increasing the financial capacity of MSMEs. The sustainability of training results requires further assistance and digital infrastructure support from the government and educational institutions.